Changes In Hematological Parameters Of Typhoid Fever Patients At Pku Bantul Hospital, Yogyakarta - Devita, Ninda; Riski, Muhammad Syafiq; Marufi, Rian (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
Background: Typhoid fever causes changes in the results of hematological examination. Many factors influence hematological changes in thyphoid fever these changes. Obective: This study aims to determine the relationship between several patient characteristics and hematological changes in typhoid fever patients at PKU General Hospital, Bantul, Yogyakarta. Method: This is a cross-sectional study. A total of 85 patients diagnosed with typhoid fever at PKU General Hospital were included in this study. Hematological examination results and subject characteristics (sex, age, duration of fever) were taken from medical records. The relationship between subject characteristics and hematological changes was analyzed by Chi-Square test using Medcalc software. Result:  Anemia and leukopenia were found to be higher in female subjects (34.88% vs 17.14%; p=0.03 and 20.45% vs 9.75%; p=0.04). Age â‰¥45 years are associated with the incidence of anemia (18.61 vs 40.00; p=0.03). Leukopenia and thrombocytosis was higher in patients with a duration of fever < 1 week (p=0.02 and p=0.000). Conclusion: Hematological changes in thyphoid fever are influenced by gender, age, and duration of fever before admission to the hospital. Keywords: Typhoid fever, Hematological changes, Factor influenced